Bibliometric analysis of scientific literature on intestinal parasites in Argentina during the period 1985-2014 - Basualdo Farjat, Juan Ángel (2016)
The study of scientific production is a good indicator of the progress in research and knowledge generation. Bibliometrics is a scientific discipline that uses a set of indicators to quantitatively express the bibliographic characteristics of scientific publications. The scientific literature on the epidemiology of intestinal parasites in Argentina is scattered in numerous sources, hindering access and visibility to the scientific community. Our purpose was to perform a quantitative, bibliometric study of the scientific literature on intestinal parasites in humans in Argentina published in the period 1985-2014. This bibliometric analysis showed an increase in the number of articles on intestinal parasites in humans in Argentina published over the past 30 years. Those articles showed a collaboration index similar to that of the literature, with a high index of institutionality for national institutions and a very low one for international collaboration. The original articles were published in scientific journals in the American Continent, Europe and Asia. The use of bibliometric indicators can provide a solid tool for the diagnosis and survey of the research on epidemiology of intestinal parasites and contributes to the dissemination and visibility of information on the scientific production developed in Argentina.